(untitled) (Colombia Medica, 1986)
We present 30 cases of hepatic abscess studied at the Hospital Universitario in Cali, Colombia, between 1981 and 1982, in which the diagnosis was confirmed by a liver scan. Diagnostic methods, therapeutic modalities and clinical behavior are discussed. In fourteen patients, a liver scan follow-up was performed in order to ascertain the resolution time of the abscesses.